Profil Soal Tes Kemampuan Berpikir Kritis Berbasis Materi Ajar Metabolisme Bagi Mahasiswa Biologi - Abd Muis; Ismail Ismail; Arifah Novia Arifin (Seminar Nasional LP2M UNM, 2019)
Teaching material-based thinking ability tests are used to assess students' critical thinking skills. The development of critical test questions on teaching materials aimed at producing valid instruments was carried out using the ADDIE development model (Analysis, Determine, Design, Implementation, Evaluate). Data collection using instrument validation test item description. The product design of the critical test questions produced was validated with a very valid category. The results of the development of the facts of critical thinking test questions based on teaching material that is implemented have a scope of material based on RPS Basic Biology, Structures related to critical thinking skills and material indicators, nine critical thinking indicators derived from Ennis, Greenstein, and Ministry of Education, The main points in the rubric are arranged as a continuum, the pattern of answering is continued by each discourse